Antioxidant Activity and Total Phenols from the Methanolic Extract of Miconia albicans (Sw.) Triana Leaves - Pieroni, Lais Goyos [UNESP]; de Rezende, Fernanda Mendes; Ximenes, Valdecir Farias [UNESP]; Dokkedal, Anne Lígia [UNESP] (Mdpi Ag, 2011)
Miconia is one of the largest genus of the Melastomataceae, with approximately 1,000 species. Studies aiming to describe the diverse biological activities of the Miconia species have shown promising results, such as analgesic, antimicrobial and trypanocidal properties. M. albicans leaves were dried, powdered and extracted to afford chloroformic and methanolic extracts. Total phenolic contents in the methanolic extract were determined according to modified Folin-Ciocalteu method. The antioxidant activity was measured using AAPH and DPPH radical assays. Chemical analysis was performed with the n-butanol fraction of the methanolic extract and the chloroformic extract, using different chromatographic techniques (CC, HPLC). The structural elucidation of compounds was performed using 500 MHz NMR and HPLC methods. The methanolic extract showed a high level of total phenolic contents; the results with antioxidant assays showed that the methanolic extract, the n-butanolic fraction and the isolated flavonoids from M. albicans had a significant scavenging capacity against AAPH and DPPH. Quercetin, quercetin-3-O-glucoside, rutin, 3-(E)-p-coumaroyl-alpha-amyrin was isolated from the n-butanolic fraction and a-amyrin, epi-betulinic acid, ursolic acid, epi-ursolic acid from the chloroformic extract. The results presented in this study demonstrate that M. albicans is a promising species in the search for biologically active compounds.
Keywords: antioxidant activity; flavonoids; Miconia albicans; total phenolic contents